Flail Chest Fracture of Ribs 2-9 with Post-CTT Lung Contusion and Subcutaneous Emphysema: A Case Report - Kalih Sarjono; Urip Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2024)
Flail chest fracture of ribs 2-9 with pulmonary contusion after CTT installation and subcutaneous emphysema is a serious condition that affects the patient's respiratory function and quality of life. Patients often experience difficulty breathing, increased respiratory rate, and severe chest pain. In addition, the presence of a flail chest can increase the risk of complications such as atelectasis, lung infections, and hypoxia. The combination of this disease accompanied by rib fractures 2-9, subcutaneous emphysema, pneumothorax, and hemothorax makes this case unique and rare, so this finding can shed new light on the possible pathogenesis of a disease or its bad effects. The aim of this study is to describe the action in cases of Flail chest fracture of ribs 2-9 with post CTT pulmonary contusion and subcutaneous emphysema. Mr. T, a 23 year old man, was admitted to the Kemuning ICU with various medical diagnoses including flail chest, rib fracture, emphysema subcutis, right pneumothorax, pleural effusion, right hemothorax, right lung contusion, and ARDS. The patient complained of shortness of breath and chest pain after a motorbike accident. Initial actions include GCS monitoring, vital signs, oxygen therapy, fluid therapy, and Chest Tube Thoracostomy (CTT) installation. The patient's condition worsened and required intubation and a ventilator, then a thoracotomy operation and wire installation were performed to stabilize the fracture. After surgery, the patient's condition improved, he was successfully weaned off the ventilator, and pain was managed with intravenous morphine and ketorolac therapy. This case highlights the complexity in flail chest management that requires careful monitoring, interprofessional collaboration, and appropriate treatment strategies to improve the outcomes of patients with this condition.